2015
DOI: 10.1039/c4ew00073k
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient desalination by forward osmosis using responsive ionic liquid draw solutes

Abstract: New thermally responsive ionic liquid draw solutes generate high flux against seawater with substantially reduced electrical energy consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 41 publications
1
98
0
Order By: Relevance
“…A relative high initial flux of 9.7 LMH is observed, suggesting that STPH is a good candidate for seawater desalination by a FO process. This FO performance with the STPH draw solution was also benchmarked against most other reported draw solutes under comparable conditions, including dendrimers [18], hydroacid complexes [16,28], polyelectrolytes [29,30], responsive ionic liquid [31], and thermoresponsive copolymers [32,33]. Table 1 shows that the STPH draw solution exhibits superior FO performance to most of the other reported organic draw solutes.…”
Section: Forward Osmosis (Fo) Performancementioning
confidence: 97%
“…A relative high initial flux of 9.7 LMH is observed, suggesting that STPH is a good candidate for seawater desalination by a FO process. This FO performance with the STPH draw solution was also benchmarked against most other reported draw solutes under comparable conditions, including dendrimers [18], hydroacid complexes [16,28], polyelectrolytes [29,30], responsive ionic liquid [31], and thermoresponsive copolymers [32,33]. Table 1 shows that the STPH draw solution exhibits superior FO performance to most of the other reported organic draw solutes.…”
Section: Forward Osmosis (Fo) Performancementioning
confidence: 97%
“…35 Their results showed that LCST-type of ILs were able to draw water from feed solutions up to a 1.6 M salt concentration at room temperature, and regenerate at high temperature when phase separation was induced.…”
Section: Introductionmentioning
confidence: 98%
“…Owing to their ionic character, ILs have a number of desirable attributes, such as negligible vapor pressure, high ionic conductance, and often high thermal and chemical stability [1][2][3][4] . The physicochemical properties of ionic liquids can be tailored by chemical modification of the cation and/or anion, leading to a vast number (>10 14 ) of distinct ionic liquid combinations 5 . This presents an enormous library of ionic liquids to fully explore.…”
mentioning
confidence: 99%
“…A subclass of ionic liquids undergoes a thermoresponsive liquid-liquid phase transition of either an upper critical solution temperature (UCST) or lower critical solution temperature (LCST). Such thermoresponsive IL-based mixtures have opened up new potential applications such as protein extraction [10][11][12] , metal ion extraction 13 , and forward osmosis draw solutes for water purification [14][15][16][17][18] .…”
mentioning
confidence: 99%